Low-Temperature Oxidation Induced Phase Evolution with Gradient Magnetic Heterointerfaces for Superior Electromagnetic Wave Absorption - He, Zizhuang; Shi, Lingzi; Sun, Ran; Ding, Lianfei; He, Mukun; Li, Jiaming; Guo, Hua; Gao, Tiande; Liu, Panbo (Nano-Micro Letters, 2024)
Gradient magnetic heterointerfaces have injected infinite vitality in optimizing impedance matching, adjusting dielectric/magnetic resonance and promoting electromagnetic (EM) wave absorption, but still exist a significant challenging in regulating local phase evolution. Herein, accordion-shaped Co/Co3O4@N-doped carbon nanosheets (Co/Co3O4@NC) with gradient magnetic heterointerfaces have been fabricated via the cooperative high-temperature carbonization and low-temperature oxidation process. The results indicate that the surface epitaxial growth of crystal Co3O4 domains on local Co nanoparticles realizes the adjustment of magnetic-heteroatomic components, which are beneficial for optimizing impedance matching and interfacial polarization. Moreover, gradient magnetic heterointerfaces simultaneously realize magnetic coupling, and long-range magnetic diffraction. Specifically, the synthesized Co/Co3O4@NC absorbents display the strong electromagnetic wave attenuation capability of − 53.5 dB at a thickness of 3.0 mm with an effective absorption bandwidth of 5.36 GHz, both are superior to those of single magnetic domains embedded in carbon matrix. This design concept provides us an inspiration in optimizing interfacial polarization, regulating magnetic coupling and promoting electromagnetic wave absorption. Highlights: 1 Co/Co3O4@NC nanosheets with gradient magnetic heterointerfaces have been fabricated by the high-temperature carbonization/low-temperature oxidation processes. 2 Experimental and theoretical simulation results indicate that magnetic heterointerfaces engineering is beneficial for optimizing impedance matching and promoting electromagnetic wave absorption. 3 Gradient magnetic heterointerfaces with magnetic-heteroatomic components realize the adjustment of interfacial polarization, magnetic coupling, and long-range magnetic diffraction.